2020
DOI: 10.1186/s12933-020-01157-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of admission high-sensitivity C-reactive protein in acute myocardial infarction patients with and without diabetes mellitus

Abstract: Background High-sensitivity C-reactive protein (hs-CRP) elevation frequently occurs in acute myocardial infarction (AMI) and is associated with adverse outcomes. Since diabetes mellitus (DM) is characterized by an underlying chronic inflammation, hs-CRP may have a different prognostic power in AMI patients with and without DM. Methods We prospectively included 2064 AMI patients; hs-CRP was measured at hospital admission. Patients were grouped according to hs-CRP quartiles and DM status. The primary endpoint … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…We also observed higher levels of hsCRP with increasing hs-cTnT levels. In a recent study, Lucci et al prospectively followed 2064 patients with acute myocardial infarction and found that hsCRP levels predicted mortality and were correlated with hs-cTnI both in patients with and without diabetes [ 42 ]. Although the link between CRP and SMN in stable patients warrants further investigation adjusting for hsCRP did not change the association of hs-cTnT in our prediabetic cohort (Additional file 1 : Tables S1–S3).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed higher levels of hsCRP with increasing hs-cTnT levels. In a recent study, Lucci et al prospectively followed 2064 patients with acute myocardial infarction and found that hsCRP levels predicted mortality and were correlated with hs-cTnI both in patients with and without diabetes [ 42 ]. Although the link between CRP and SMN in stable patients warrants further investigation adjusting for hsCRP did not change the association of hs-cTnT in our prediabetic cohort (Additional file 1 : Tables S1–S3).…”
Section: Discussionmentioning
confidence: 99%
“…In various populations low-grade inflammation has indeed been related to a higher risk of cardiovascular events and cardiovascular mortality [ 15 17 ]. In acute myocardial infarction patients with and without DM, hs-CRP predicts in-hospital outcome and two-year mortality [ 18 ]. It has also been shown that lowering low-grade inflammation in patients with coronary artery disease with or without type 2 diabetes reduces the residual risk for cardiovascular events [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significantly elevated initial C-reactive protein (CRP) values in the CS cohort indicate a marked systemic inflammatory response in these patients. Elevated CRP levels represent a prognostically unfavourable situation, as it has been proven to be predictable for increased rates of adverse cardiac events, poor in-hospital outcomes, acute kidney injury, and mortality [ 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%